Volcanic Hazard Assessment for an Eruption Hiatus, or Post-eruption Unrest Context: Modeling Continued Dome Collapse Hazards for Soufrière Hills Volcano - Spiller, Elaine T.; Wolpert, Robert L.; Ogburn, Sarah E.; Calder, Eliza S.; Berger, James O.; Patra, Abani K.; Pitman, E. Bruce (Frontiers in Earth Science, 2020)
Effective volcanic hazard management in regions where populations live in close proximity to persistent volcanic activity involves understanding the dynamic nature of hazards, and associated risk. Emphasis until now has been placed on identification and forecasting of the escalation of activity, in order to provide adequate warning. However, understanding eruption hiatus and post-eruption unrest hazard, or how to quantify hazard after the end of an eruption, is equally important and often key to post-eruption recovery. Unfortunately, in many cases when the level of activity lessens, the hazards, although reduced, do not necessarily cease. This is due to both the imprecise nature of determination of the ``end'' of an eruptive phase as well as to the possibility that post-eruption hazardous processes may continue to occur. An example of this is continued dome collapse hazard from lava domes which have ceased to grow, or sector collapse of a volcano. We present a new probabilistic model for forecasting pyroclastic density current (PDC) activity that takes into account the heavy-tailed distribution of the lengths of eruptive phases, the periods of relative quiescence, and the desired forecast window of interest. Further we combine this model with physics-based simulations of PDCs at Soufrière Hills to produce a series of probabilistic hazard maps that offer evidence-based guidance for dome collapse hazards that can be used to inform decision-making around access and reoccupation in areas around the volcano.